Mapping of rock resistivity value using geoelectrical method Schlumberger configuration in Solok Regency, West Sumatera - Elsi Ariani; Akmam Akmam (Universitas Sebelas Maret, 2019)
Mapping of rock resistivity value is useful for knowing the potential of the natural wealth contained in the earth. Investigation of resistivity value in Solok Regency is using 3 lines. The first line is at S 00055'0.7